Information features laboratory information system «Uranium» - S. V. Zyablitsev; V. V. Novoselskaya; P. A. Chernobrivtsev (Zaporožskij Medicinskij Žurnal)
Determined the importance of the implementation of laboratory information system in the laboratory, the main principles of information on the characteristics of the laboratory information system «URANIUM».